Roundtable - Pentecostalism and development practice - Haustein, J.; Rakodi, C.; Akhazemea, D.; Battcock, M.; James, R.; Währisch-Oblau, C. (PentecoStudies, 2015)
This article revisits central questions arising from Pentecostal actors' development practices. These were raised during the final panel discussion of the 2014 GloPent conference on "Pentecostalism and Development". The four panel participants, all development actors from various organisational and religious backgrounds, considered whether Pentecostal approaches to development work are distinctive, as well as identifying various benefits that can be gained from the engagement of Pentecostal churches in development and some challenges that arise during collaboration between development actors and Pentecostal churches. The discussion was conducted through two rounds of statements by the panel participants, complemented by editorial comments and reflections. It concludes that neither the Pentecostal approach to development nor Pentecostal churches' links with development actors are necessarily distinctive. However, more exchanges are needed between Pentecostal organisations and their members, development practitioners working with Pentecostal churches and scholars of the Pentecostal movement to improve development work among Pentecostals, links between Pentecostals and other development actors and scholarly awareness of the most salient issues. © Equinox Publishing Limited, Office 415, The Workstation, 15 Paternoster Row, Sheffield S1 2BX.
Paid
Keywords: Development; Dfid; Intrac; Pentecostalism; Rccg; United evangelical mission